Home bias in sovereign exposure and the probability of bank default: Evidence from EU stress test data - Dominik Meyland; Dorothea Schäfer (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
Since the European debt crisis economists and politicians discuss intensively the sovereign-bank nexus. The high activity in sovereign bond issuance required to mitigate the burden of the Covid19 crisis will rather intensify this debate than calm it down. Surprisingly, however, we still have only limited knowledge about the impact of a home bias in sovereign exposure on bank stability. This paper provides a new way to use European stress test data to study this relationship. In addition, we explore the effect on a bank's probability of default if the existing capital requirement privilege for EU sovereign exposures were abolished. Our results support the conceptual idea behind the nexus theory. Interestingly, the effect of a home bias on bank stability is contingent on the home country's solvency. If the home country is sufficiently solvent, investments in home sovereign bonds may improve bank stability. The findings clearly support the benefits of additional CET1 capital buffers. Regulation focusing on the home bias should account for heterogeneous effects depending on the home country's solvency.
Keywords: G21; G28; K15; 330; Home Bias; Sovereign Bonds; Bank Stability; Equity Requirements; Financial Regulation